2004
DOI: 10.1097/00131746-200405000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of a Diagnosis of Borderline Personality Disorder

Abstract: There are compelling reasons to make the diagnosis the subject of open examination and discussion between clinician and patient, and reasons to believe that disclosure would serve to advance the patient in his or her recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 38 publications
1
32
0
6
Order By: Relevance
“…In general psychiatry outpatient programs, studies have indicated that clinicians are reluctant to make a diagnosis of BPD in routine interviews, with significantly higher yields for personality disorders including BPD when structured interviews are performed (Paris, 2007;Zimmerman & Mattia, 1999). Though it is rare these days, clinicians in college and university mental health settings, meanwhile, face several possible obstacles in the accurate assessment and treatment of BPD in the student population (Hersh, 2008;LeQuesne & Hersh, 2004). Clinicians who are either unfamiliar with personality disorder diagnoses or who have orientations which do not include personality disorder diagnoses (e.g., clinicians who conceptualize personality disorders as undiagnosed primary mood disorders or clinicians who do not use standard descriptive psychiatric terminology, e.g., labeling students simply as "rejection sensitive" or "a cutter") may overlook the borderline diagnosis.…”
Section: Making the Diagnosis Of Borderline Personality Disordermentioning
confidence: 99%
“…In general psychiatry outpatient programs, studies have indicated that clinicians are reluctant to make a diagnosis of BPD in routine interviews, with significantly higher yields for personality disorders including BPD when structured interviews are performed (Paris, 2007;Zimmerman & Mattia, 1999). Though it is rare these days, clinicians in college and university mental health settings, meanwhile, face several possible obstacles in the accurate assessment and treatment of BPD in the student population (Hersh, 2008;LeQuesne & Hersh, 2004). Clinicians who are either unfamiliar with personality disorder diagnoses or who have orientations which do not include personality disorder diagnoses (e.g., clinicians who conceptualize personality disorders as undiagnosed primary mood disorders or clinicians who do not use standard descriptive psychiatric terminology, e.g., labeling students simply as "rejection sensitive" or "a cutter") may overlook the borderline diagnosis.…”
Section: Making the Diagnosis Of Borderline Personality Disordermentioning
confidence: 99%
“…20,58 Informing patients may also help to prevent misunderstandings about the diagnosis and to avoid improper treatments in the future.…”
mentioning
confidence: 99%
“…Lequesne and Hersh (2004), in their review of the literature on the advantages and disadvantages of disclosing a diagnosis of borderline personality disorder to the client, note that this diagnosis is often withheld due to concern about the potential for distress, as well as transference/countertransference issues common in the treatment of these patients. In contrast, diagnoses of attention deficit hyperactivity disorder (ADHD) and Asperger's syndrome are often shared with patients as a way to help them manage their lives (Huws & Jones, 2008).…”
Section: The Right To Knowmentioning
confidence: 99%